Produksi Pigmen Merah Monascus sp. pada Substrat Tepung Biji Durian (Durio zibethinus Murr.) dan Biji Nangka (Artocarpus heterophyllus Lam.) dengan Variasi Penambahan Sumber Nitrogen - Tsania Dyna Falasifa; Agung Suprihadi; Sri pujiyanto (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
Public awareness about the danger of using synthetic dyes impact on health for a long term, pushes the demand of natural dye that is healthier. One of the natural dye is Monascus sp. red pigment which traditionally uses the rice substrate. Durian seed and jackfruit seed are residue from agroindustry which still have high nutritional value thus potentially become the alternative substrate. The aim of this study was to measured Monascus sp. red pigment production in the flour substrate of durian seed and jackfruit seed with variant nitrogen source added. This research used completely randomized design (CRD) factorial with 2 factors. The first factor was a kind of substrate fermentation (N): jackfruit seed flour and (D): durian seed flour. The second factor was concentration peptone added (P0): 0%, (P1): 1%, (P2): 2%, and (P3): 3%. Research consist of 8 treatments with 3 replications. Research parameters were red pigment concentration and biomass estimation. Analysis of the data used Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at the 95% significance level and Pearson correlation test. The result showed that Monascus sp. can grew and producted red pigment on both of substrate with the addition of a nitrogen source variation. Fermentation on the jackfruit seed flour substrate with 2% peptone added was the most effective in red pigment production with 5,55 CVU/gds. The addition of 2% peptone on both types of substrate yielded highest biomass with 1.53 mg/gds, and there was a positive correlation between the biomass and the red pigment production. Keywords: Pigment, Monascus sp., Durio zibethinus, Artocarpus heterophyllus, nitrogen